(untitled) (Applied Biological Research, 2012)
The present study was aimed to document the genetic variability in wild genotypes of pomegranate in central Kashmir. On the basis of morphological and physicochemical characters, 33 genotypes were identified during intensive survey in districts Srinagar, Ganderbal and Budgam in 2009-2010. Remarkable variability was observed amongst the genotypes for traits like plant height, plantspread, yield, fruit length, diameter and weight, total aril weight, rind thickness, TSS, juice content, acidity, ascorbic acid, reducing sugars, total sugar and anthocyanin contents. On the basis of yield and quality, 7 best genotypes were selected for use in future pomegranate improvement programme.